ANALISIS BUKU “DARI BENIH KE POHON CEDAR” DALAM PENERAPAN PROPHETIC PARENTING - Chandra Dewi; Titi Latifah Nurullah; Shalsa Syawalia; Alifah Adzani; Putri Jasmine; Cindy Nurmala (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Parenting in Islam is important to learn because it teaches a lot about how parents educate children in accordance with Islamic teachings. Like wanting to plant a tree that starts from seed, the seed you want to plant should be good so that the plant to be planted becomes good and full of blessings. Someone who wants to start a household should pay attention to several things that can trigger the wrong parenting style to avoid and create a healthy family. The purpose of this research is to identify indicators of improper parenting, the impact of wrong parenting on child development, and steps to implement good parenting according to Islam. The research methodology used is Literature Review, with the aim of collecting, summarizing, and analyzing findings from previous research. Based on the findings of this study, according to the Islamic view, it starts from choosing a partner in the household and the role of parents in educating children. It is important for parents to balance the skills in educating and nurturing children with good parenting and caring in overcoming the problems experienced by their children so that the two things become a balanced whole. Islamic parenting has an important role to play in educating children, focusing on the pre-conception, prenatal, and post-natal periods. Good parenting according to Islam starts from covering the selection of partners in the household, the role of both parents in educating children, and the provision of education and tarbiyah.